2011
DOI: 10.1002/app.33862
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of reactive blocked‐isocyanate coupling agents from methyl ethyl ketoxime, ethyl cellosolve/ε‐caprolactam blocked aromatic and aliphatic diisocyanates

Abstract: A series of water-dispersible blocked polyisocyanates were synthesized from toluene 2,4-diisocyanate (TDI), isophorone diisocyanate (IPDI), dimethylol propionic acid, methyl ethyl ketoxime (MEKO), ethyl cellosolve (EC), and e-caprolactam (CL). The physical properties, such as the viscosity, pH, and storage stability, of the blocked-polyisocyanate adducts were measured. All aqueous dispersions of the blocked polyisocyanates showed good storage stability. The prepared blocked polyisocyanates were characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 49 publications
(51 reference statements)
0
16
0
Order By: Relevance
“…EC‐blocked polyisocyanate (EC‐bp) and hydroxyl‐terminated polyurethane emulsion (PU) were prepared in our lab. They were prepared according to the procedure reported in our previous work 22. The maximum deblocking temperature was around 150°C.…”
Section: Methodsmentioning
confidence: 99%
“…EC‐blocked polyisocyanate (EC‐bp) and hydroxyl‐terminated polyurethane emulsion (PU) were prepared in our lab. They were prepared according to the procedure reported in our previous work 22. The maximum deblocking temperature was around 150°C.…”
Section: Methodsmentioning
confidence: 99%
“…Duplicate experiments were conducted for each set of mixture to ensure the accuracy of the collected data. 51 2.3.9 | Atomic force microscopy…”
Section: Mechanical Properties By Tensile Testingmentioning
confidence: 99%
“…According to literature reports, the storage time at room temperature can even reach 6 months. 51 In the presence of a suitable co-reactant, BPUP was unblocked when heated, and then the chain extension reaction was allowed to proceed. Finally, polyurethane materials with better properties were obtained by casting molding process.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that structures of blocking agents and isocyanates equally have a strong influence on deblocking temperature (1,(15)(16)(17). Several compounds, having active hydrogen atom, have been reported as blocking agents, including phenols, oximes, amides, imides, imidazoles, amidines, pyrazoles, N-methyl anilines, and active methylene compounds (1,2,(15)(16)(17)(18)(19)(20)(21). It has been reported that substituent present in the blocking agent has a very strong influence on the deblocking temperature.…”
Section: Introductionmentioning
confidence: 98%